PERBEDAAN KEMAMPUAN KOGNITIF SISWA MENGGUNAKAN MODEL KOOPERATIF TIPE JIGSAW DENGAN STAD DI SEKOLAH DASAR - Afniati, Afniati; Masniladevi, Masniladevi; Zuryanty, Zuryanty (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2014)
AbstractThe purpose of this research was to compare to know the difference of students' cognitive ability using model cooperative Jigsaw type with model cooperative STAD type in the fourth grade of primary school. The design form of this research is quasi experimental. The technique sampling is total sampling and determining to class samplel with random.The study sample used 30 students for the class using the model cooperative Jigsaw type and 28 students for the class using the model cooperative STAD type. The data analysis of both groups uses t test, the result of tct 2,462 and ttable at significant level α = 0,05 2,003, ttest > ttable. This shows significant differences in students' cognitive abilities by using model cooperative Jigsaw type with model cooperative STAD type in Grade IV of primary school.Keywords: Jigsaw and STAD, cognitive abilities.